(untitled) (Global Media Journal - German Edition, 2022)
This article examines online violence disguised as humor on Turkish digital media plat forms. Online conversations from Sour Dictionary, a pioneer dictionary-platform, reveal how class, politics and gender inequalities intersect to reproduce power relations in digital media against non-paid domestic workers (housewives) being visible in Facebook. Drawing from the theoretical framework of intersectionality, the study shows that women are exposed to violence not just through the category of gender, while at the same time, the criticism and the violence interchange dynamically through the instrument of humor.